"But a champion comes out much, much later": A sport development case study of the 1968 U.S. Olympic team. Issue 4 (August 2018) - Berg, Brennan K.; Fuller, Rhema D.; Hutchinson, Michael
Highlights: We examined elite athlete sport development from a different historical period. 59 interviews were conducted with 1968 U.S. Olympians. Attraction, retention, and transition were similar and different to modern sport. Results suggest some sport development principles could remain constant. Abstract: Increasing attention has been given to the effective development of elite athletes. In this inquiry, the authors used a historical case study to ascertain the ways elite athletes were developed in a different era of sport in the United States. Using the attraction, retention, and transition frameworks, the factors that fostered the development of athletes from the 1968 Summer Olympics were drawn out through oral history interviews. In total, interviews with 59 U.S. Olympians were conducted. The results reveal how the athletes experienced supportive recruitment and retention environments, were able to manage the difficulty of developing elite talent, and encountered both challenges and opportunities transitioning through and out of elite sport. This analysis demonstrates how sport development principles are diverse in their temporal relevance and reinforce the practical implications meant to serve the modern athlete. Further, at least some sport development principles could remain constant regardless of how context and elite athlete experiences evolve in the future.